2011
DOI: 10.1158/0008-5472.can-10-2733
|View full text |Cite
|
Sign up to set email alerts
|

Replication and Functional Genomic Analyses of the Breast Cancer Susceptibility Locus at 6q25.1 Generalize Its Importance in Women of Chinese, Japanese, and European Ancestry

Abstract: We evaluated the generalizability of a single nucleotide polymorphism (SNP), rs2046210 (A/G allele), associated with breast cancer risk that was initially identified at 6q25.1 in a genome-wide association study conducted among Chinese women. In a pooled analysis of more than 31,000 women of East-Asian, European, and African ancestry, we found a positive association for rs2046210 and breast cancer risk in Chinese women [ORs (95% CI) ¼ 1.30 (1.22-1.38) and 1.64 (1.50-1.80) for the AG and AA genotypes, respective… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
71
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(83 citation statements)
references
References 27 publications
9
71
3
Order By: Relevance
“…At present, there are no data on possible correlations between clinicopathological characteristics and common low-penetrance BC susceptibility alleles in MBC. On the other hand, in FBC, there is increasing evidence that associations between common variants and BC risk could vary by clinically important tumor characteristics, mainly by ER expression [25][26][27][28][29][30][31]. We found that ESR1 was significantly associated with the risk of ER-BCs in males.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…At present, there are no data on possible correlations between clinicopathological characteristics and common low-penetrance BC susceptibility alleles in MBC. On the other hand, in FBC, there is increasing evidence that associations between common variants and BC risk could vary by clinically important tumor characteristics, mainly by ER expression [25][26][27][28][29][30][31]. We found that ESR1 was significantly associated with the risk of ER-BCs in males.…”
Section: Discussionmentioning
confidence: 57%
“…and ER-disease [25,27]. On the other hand, variants in ESR1 and 19p13 show evidence of an association primarily with ER-BCs [20,[29][30][31]. At present, there are no data on possible correlations between clinicopathological characteristics and common low-penetrance BC susceptibility alleles in MBC.…”
Section: Introductionmentioning
confidence: 96%
“…In addition, there is no transcriptional factor binding site on rs2046210. 5 The mechanisms by which SNP rs2046210, or SNPs in LD with it, promote disease risk have remained elusive.…”
Section: C6orf97-esr1 Susceptibility Locus In Breast Cancermentioning
confidence: 99%
“…For instance, novel studies on the role of ancestry in cancer susceptibility [19][20][21][22] has prompted the need for centralized collection of DNA from blood of consented individuals, an activity that will be added onto the current procedures but which would require additional infrastructure to be developed. Other future plans of the PRTB include increased research collaborations among investigators from the partnering institutions and from other institutions; continued development of IT technologies to ensure appropriate and secure management of the data; expansion on the current use of the many caTissue and caBIG capabilities; development of a disaster recovery plan including regular data transfers to the MCC for redundancy in case of natural disasters; increased number of hospitals and community physicians involved in tissue accrual; and extension of the accrual process to liquid biospecimens.…”
Section: Flores Et Almentioning
confidence: 99%